Opini Audit BPK-RI dan Substansi Kinerja Keuangan Pemerintah Daerah Kota/Kabupaten di Provinsi Kalimantan Barat - Zulkarnain Zulkarnain; Rezka Andriansyah (Cakrawala Repositori IMWI, 2018)
This study aims to examine whether any significant differences the financial performance of the local city/regency government who gets unqualified audit opinion and qualified audit opinion. The financial performance of the local city/regency government measured by APBD financial ratios such as regional independence ratio, effectiveness ratio, effeciency ratio, activity ratio, and growth ratio. This study employs publicly available data from financial database of a sample of 14 local city/regency government-year in West Kalimantan Province, Indonesia for the years of 2012-2016. Using independent sample test, this study finds that there are no significant differences the financial performance of the local city/regency government who gets unqualified audit opinion and qualified audit opinion, except for regional independence ratio.